Workshop cluster 1(+)γδ T-cell receptor(+) T cells from calves express high levels of interferon-γ in response to stimulation with interleukin-12 and -18 - Price, Sally J (Blackwell Publishing Inc, 2007)
γδ T-cell receptor(+) T lymphocytes are an important element of the innate immune system. Early production of interferon (IFN)-γ by γδ T cells may have a role in linking innate and adaptive immune responses and contribute to T helper-1 bias. We investigated the role of cytokines in the activation and induction of IFN-γ secretion by bovine workshop cluster 1(+) (WC1(+)) γδ T cells. The effects of culture with interleukin (IL)-12, IL-18, IL-15 and IL-2 were investigated; these cytokines are known to influence murine and human γδ T cells. We report that bovine WC1(+)γδ T cells are synergistically stimulated by IL-12 and IL-18 to secrete large quantities of IFN-γ. Neonatal calves were shown to have significantly higher numbers of circulating WC1(+)γδ T cells than adult animals. In addition, the response of peripheral blood WC1(+)γδ T cells was significantly higher in neonatal calves compared with adult animals. However, in adult animals the response of lymph node WC1(+)γδ T cells to IL-12/IL-18 was more pronounced than that of peripheral blood WC1(+)γδ T cells. We hypothesize that the induction of IFN-γ secretion from WC1(+)γδ T cells by IL-12 and IL-18 is likely to be an important element of the innate response to pathogens such as Mycobacterium bovis. The high numbers of WC1(+)γδ T cells in neonatal calves, and their inherent ability to respond to inflammatory cytokines, could be a key factor in the enhanced responses seen in calves to BCG vaccination.